2023
DOI: 10.3389/fimmu.2023.1077088
|View full text |Cite
|
Sign up to set email alerts
|

Multisite chronic pain and the risk of autoimmune diseases: A Mendelian randomization study

Abstract: BackgroundAccumulating evidence has demonstrated that an association between chronic pain and autoimmune diseases (AIDs). Nevertheless, it is unclear whether these associations refer to a causal relationship. We used a two-sample Mendelian randomization (MR) method to determine the causal relationship between chronic pain and AIDs.MethodsWe assessed genome-wide association study (GWAS) summary statistics for chronic pain [multisite chronic pain (MCP) and chronic widespread pain (CWP)], and eight common AIDs, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The directionality of pleiotropy can be detected and adjusted using the MR-Egger technique based on the Instrument Strength Independent of Direct Effect (InSIDE) assumption, although it is underpowered ( 39 ). Additionally, the MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test was used to detect potential horizontal pleiotropy and reduce the effects of pleiotropy by eliminating outliers ( 40 ). The heterogeneity was assessed using Cochran's Q-statistic.…”
Section: Methodsmentioning
confidence: 99%
“…The directionality of pleiotropy can be detected and adjusted using the MR-Egger technique based on the Instrument Strength Independent of Direct Effect (InSIDE) assumption, although it is underpowered ( 39 ). Additionally, the MR Pleiotropy RESidual Sum and Outlier (MR-PRESSO) test was used to detect potential horizontal pleiotropy and reduce the effects of pleiotropy by eliminating outliers ( 40 ). The heterogeneity was assessed using Cochran's Q-statistic.…”
Section: Methodsmentioning
confidence: 99%
“…Eiris et al (158) showed a significant association between three SNPs (rs6887695, rs3212227 and rs2201841) and diabetes mellitus. Recent GWAS findings have indicated a genetic association between psoriasis and autoimmune diseases (such as multiple sclerosis, rheumatoid arthritis and autoimmune hypothyroidism), neuromuscular diseases (including Alzheimer's and Parkinson's diseases) (159)(160)(161)(162), chronic inflammation (163) and skin diseases (164). Future investigations will aim to conduct a transdisease meta-analysis and Mendelian randomization to determine the causal relationship between psoriasis and the aforementioned diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Following a rigorous surveillance, we narrowed our selection to 7 separate SNPs for GERD and 28 SNPs for CWP. To do this, we eliminated chain imbalances and associated confounders, with smoking being recognized as a risk factor for GERD and smoking, obesity, mental illness, cancer, and osteoarthritis as risk factors for CWP (27)(28)(29). Furthermore, SNPs that did not appear in the endpoint GWAS were deleted.…”
Section: Genetic Instrumental Variablesmentioning
confidence: 99%